Perceptions and experiences of environmental health and risks among Latina mothers in urban Los Angeles, California, USA - Elizabeth M. Kamai; Andrea Calderon; Yoshira Ornelas Van Horne; Theresa M. Bastain; Carrie V. Breton; Jill E. Johnston (BMC, 2023)
Abstract Background Environmental exposures during pregnancy and early childhood can have acute and chronic adverse health impacts. As minoritized populations are more likely to reside in areas with greater pollution, it is important to understand their views and lived experiences to inform action. The purpose of this community-driven qualitative research study was to understand how urban Latina mothers in Los Angeles County, California perceived environmental health and risks. Methods We conducted semi-structured individual interviews with Latina pregnant women and mothers of young children, recruited through existing collaborations with community organizations. Interviews conducted in either English or Spanish and were coded inductively according to a modified grounded theory approach. Results Thirty-six Latina mothers completed interviews between August-October 2016. Participants lived primarily in low-income communities of South-Central Los Angeles and East Los Angeles. We identified three major themes based on the participants' responses during interviews: Defining the Environment, Environment & Health Risks, and Social & Political Responsibility. Women defined their environment in terms of both "nature" and "hazards." They consistently identified foul odors, dirtiness, noise, trash, bugs, smoke, and other visible blights as indicators of household and neighborhood environmental hazards. They expressed fear and uncertainty about how their environment could affect their health and that of their children, as well as specific concerns about respiratory health, asthma, allergies, cancer, and adverse pregnancy outcomes. Mothers often changed individual behaviors around diet and cleaning during pregnancy but were frustrated by power imbalances that left them unable to change their home or neighborhood environments, despite their desire to do so. Discussion Our study is among the first to describe how urban Latina mothers perceive and experience environmental health risks during pregnancy and early childhood. Our research suggests additional attention is needed by public health professionals and researchers to address the environmental health risks that matter most to urban Latina mothers. They also highlight the tension that many urban Latina mothers feel between wanting to protect their families' health and well-being and feeling powerless to change their environment. Broad policy changes, rather than additional individual recommendations, are needed to address the concerns of this vulnerable population.